2012
DOI: 10.1021/ja208316h
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein Induces Both Positive Mean Curvature and Negative Gaussian Curvature in Membranes

Abstract: Using a combination of X-ray scattering, fluorescence correlation spectroscopy, coarse-grained molecular dynamics (MD) simulations and potential of mean force calculations, we have explored the membrane remodeling effects of monomeric α-synuclein (αS). Our initial findings from multiple approaches are that αS (1) causes a significant thinning of the bilayer and (2) stabilizes positive mean curvature, such that the maximum principle curvature matches that of synaptic vesicles, αS-induced tubules, and the synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
176
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(181 citation statements)
references
References 64 publications
4
176
0
1
Order By: Relevance
“…As expected, the headgroup density is higher in the inner leaflet due to compaction in the convex vesicle. The protein has very little effect on bilayer structure, partitioning to a similar depth as previous studies (6,9,10,17), with no notable change in bilayer thickness (Fig. S1 in the Supporting Material).…”
supporting
confidence: 72%
See 1 more Smart Citation
“…As expected, the headgroup density is higher in the inner leaflet due to compaction in the convex vesicle. The protein has very little effect on bilayer structure, partitioning to a similar depth as previous studies (6,9,10,17), with no notable change in bilayer thickness (Fig. S1 in the Supporting Material).…”
supporting
confidence: 72%
“…The protein is simulated as a single, extended a-helix whose secondary structure is fixed. While conformational heterogeneity of the protein has recently been noted (15), we have shown that it has little effect on protein partition depth or membrane curvature (10). We have simulated DPPC vesicles in the fluid-phase, rather than the more complex quaternary mixture, for several reasons (discussed at length in the Supporting Material).…”
mentioning
confidence: 99%
“…This latter effect can also be related to the lateral expansion of the lipid molecules that induces membrane thinning and, with further insertion of protein into the membrane, causes lipid expansion out of the membrane plane of the bilayer or, as previously reported, formation of positive curvature to relieve excess surface pressure (56,57). A close relationship between amphipathic helix insertion and membrane deformation has been established (57), and ␣-Syn has been reported to induce positive curvature of the membrane and the formation of tubular structures (26,58,59). Recently, these remodeling processes caused by ␣-Syn binding have been proposed to induce the formation of lipoprotein nanoparticles (60).…”
Section: Discussionmentioning
confidence: 53%
“…Nevertheless, it has been shown that curvature selectivity by aSyn cannot be comprehensively characterized through measurements of affinity alone (54), and further studies will be required to evaluate more directly the curvature selectivity of Ac-aSyn. In addition, it is now generally accepted that aSyn can influence membrane properties, specifically curvature, in addition to sensing them (57,58,60,62,63,66,75,83), and the influence of N-terminal acetylation on this activity of the protein remains to be explored.…”
Section: Discussionmentioning
confidence: 99%